2019
DOI: 10.3390/molecules24142560
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Autofluorescence—How Does It Affect Parathyroid and Thyroid Surgery? A 5 Year Experience

Abstract: Injury to parathyroid glands during thyroid and parathyroid surgery is common and postoperative hypoparathyroidism represents a serious complication. Parathyroid glands possess a unique autofluorescence in the near-infrared spectrum which could be used for their identification and protection at an early stage of the operation. In the present study parathyroid autofluorescence was visualized intraoperatively using a standard Storz laparoscopic near-infrared/indocyanine green (NIR/ICG) imaging system with minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
2
40
1
2
Order By: Relevance
“…This property enables a charge-coupled device camera to record the fluorescence of ICG molecules [78]. Thus, this characteristic has been applied in the visualization of PGs since the fluorescence intensity of the glands can be measured by the ICG fluorescence angiography (ICGA) [74,126,127]. ICG is a nonselective agent, which constitutes a limitation of its intraoperative application in PGs detection since it does not target parathyroid parenchyma specifically.…”
Section: Indocyanine Greenmentioning
confidence: 99%
“…This property enables a charge-coupled device camera to record the fluorescence of ICG molecules [78]. Thus, this characteristic has been applied in the visualization of PGs since the fluorescence intensity of the glands can be measured by the ICG fluorescence angiography (ICGA) [74,126,127]. ICG is a nonselective agent, which constitutes a limitation of its intraoperative application in PGs detection since it does not target parathyroid parenchyma specifically.…”
Section: Indocyanine Greenmentioning
confidence: 99%
“…Tummers et al used methylene blue and near infrared imaging for detection of parathyroids [10]. Recently, it was reported that parathyroid, and to a lower extent thyroid, emit a unique autofluorescence signal in the near infrared region [11][12][13][14]. A few studies [15][16][17][18][19] reported the optical coherence tomography (OCT) to be a fairly reliable method for parathyroid identification, showing that representative tissue structures were visible in the OCT images, in both ex vivo [15] and in vivo [16] investigations.…”
Section: Introductionmentioning
confidence: 99%
“…More recent use of NIR-imaging camera systems has the advantage of enabling contactless working and provides a large surgical field of view. Ladurner et al modified a commercially available NIR imaging system (Karl Storz SE & Co. KG, Tuttlingen, Germany), which was originally designed for indocyanine green (ICG) imaging, applicable in laparoscopic surgery and showing PTG detection rates of 81.0%-93.3% [100][101][102]. A similar setup was successfully used in a study conducting video-assisted neck surgery (n = 5) with combined use of NIR imaging for PTG detection and ICG imaging to prove vascular supply [103].…”
Section: Af Of the Thyroid And Parathyroid Glandsmentioning
confidence: 99%
“…Furthermore, it is probably only a single molecule that is excited by NIR light, as the excitation maximum was found to be in a narrow wavelength range (814−826 nm) [95]. Calcium-sensing receptors and vitamin D receptors are the repeatedly hypothesized PTG fluorophore candidates, based on their expression in PTGs, surrounding tissues, and other organs [98,101]. However, scientific proof is still pending.…”
Section: Biomolecules Acting As Endogenous Fluorophoresmentioning
confidence: 99%
See 1 more Smart Citation